Iceland : 2013 Article IV Consultations and Third Post-Program Monitoring Discussions. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation highlights that Iceland's economy is on a path to recovery, but legacy vulnerabilities are weighing on growth. GDP growth-which reached 2.9 percent in 2011-slowed to 1.6 percent in 2012 amid private sector deleveraging and weak external demand. Unemployment has continued to decline however, standing at 5.1 percent in May, down from a peak of 9.2 percent in September 2010. Inflation has come down to 3.3 percent in June from a peak of 18.6 in January 2009, but remains above the central bank's target of 2 1\2 percent. The outlook is for modest growth, declining inflation, and improving fiscal and external position.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet